An Evaluation Framework for The Adoption of Big Data Technologies in Higher Educational Institutions - Jude Odiakaosa Osakwe; Martin Ujakpa; Mercy Ziezo; Gloria Iyawa (Universitas Bina Darma, 2023)
The aim of this study is to develop a framework for the use of Big Data Technology in Higher Educational Institutions (HEIs). The research which employed a mixed method approach, is primarily based on relevant critical analysis and literature review of studies conducted within the Big Data Technology area in higher education institutions. It investigated the processes of monitoring student performance by Namibian HEIs. The challenges faced by Namibian HEIs on the use of BDT. The various methods of data collection by Namibian HEIs and determined the level of readiness to adopt BDT.in Namibian HEIs. The study further undertook quantitative surveys and qualitative interviews with staff of the three (3) higher institutions in Namibia. A sample of 345 participants from International University of Management (IUM), Namibia University of Science and Technology (NUST), and The University of Namibia comprising the study's population (UNAM) were selected for this study using the simple random sampling technique. The Unified Theory of Acceptance and Use of Technology (UTAUT) constructs model was used to analyse to collect and analyse the quantitative data collected in this study. Finally, the study developed a sustainable framework that will guide the use of Big Data Technology in Namibian Higher Educational Institutions (HEIs). The validity of the framework was ascertained by expert reviews to ensure that the framework developed is effective and appropriate in fulfilling the purpose of the study and its objectives.